Legal Education on Women’s Property Inheritance Rights in South Sumatera - Sukarti, Dewi; Asyari, Hasyim; Zulkifli, Zulkifli (Universitas Islam Negeri Jakarta, 2023)
By and large, patrilineal societies still experience the unsolved problem of women’s property disinheritance. This article attempts to examine the role of legal education on female inheritance in transforming society regarding the issue in question. Based on a qualitative inquiry in Besemah society and two prominent universities in Palembang, South Sumatera, Indonesia, this article suggests that although the state laws have protected the rights of women to inheritance in various enactments, university students and society must be educated on the laws, the society’s rights in general and the law of inheritance in particular. Universities have the potential to influence society through the socalled three devotional services of highermeducation, namely education, research, and community services. As seen in campus curricula, students can be educated through classroom education, and society can be educated through community services. Debates at the academic level on inheritance problems in society should have been seen in academic journals, as there is a considerable gap between theories in classrooms and practices of society. Unfortunately, as shown in their curriculum and publications, universities in South Sumarera do not pay enough attention to property inheritance because it is not in students’ interests. In community service activities, universities have not advocated inheritance law to enhance people’s awareness of just inheritance practices, whereas universities are traditionally known as an agent of change. Thus, in this case, universities do not change society but are changed by society. Artikel ini menunjukkan kurangnya pendidikan hukum mengenai waris perempuan menyebabkan tidak terpecahkannya persoalan waris Perempuan pada masyarakat patrilineal. Berdasarkan penelitian kualitatif pada Masyarakat Besemah dan dua universitas besar di Palembang, Sumarera Selatan, Indonesia, artikel ini menunjukkan bahwa walaupun negara sudah melindungi hak-hak waris perempuan dalam berbagai undang-undang, mahasiswa dan masyarakat perlu diberi pendidikan mengenai hukum, hak-hak masyarakat pada umumnya dan hukum waris pada khususnya. Universitas memiliki potensi untuk mempengaruhi masyarakat melalui Tridharma Perguruan Tinggi, yaitu pendidikan, penelitian, dan pengabdian kepada masyarakat. Sebagaimana terlihat dalam kurikulum kampus, mahasiswa dapat dididik melalui pengajaran di ruang kelas dan masyarakat dididik melalui pengabdian kepada masyarakat. Perdebatan di tingkat akademik tentang persoalan waris di masyarakat semestinya terlihat di jurnal-jurnal ilmiah mengingat adanya kesenjangan yang dalam antara teori-teori yang diberikan di kelas dengan praktek-praktek masyarakat. Sayangnya, sebagaimana terlihat pada kurikulum dan publikasi mereka, universitas di Sumatera Selatan tidak menaruh cukup perhatian terhadap kewarisan karena tidak menjadi minat mahasiswa. Dalam program Kuliah Kerja Nyata (KKN), universitas tidak mengadvokasi hukum waris untuk meningkatkan kesadaran Masyarakat mengenai praktek waris yang adil, padahal universitas secara tradisional dikenal sebagai sebuah agen perubahan. Jadi, dalam hal ini universitas tidak mengubah masyarakat, melainkan diubah oleh masyarakat.